Characterization of intra-cavity reflections by Fourier transforming spectral data of optically pumped InGaN lasers - Hofstetter, Daniel; Romano, Linda T.; Thornton, Robert L.; Johnson, N. M. (My University, 1997)
Fourier analysis of laser emission spectra just above threshold is used to evaluate the impact of structural defects on the emission from optically pumped InGaN lasers. By dry etching a 300-nm-deep groove into the surface of a laser bar, we have modified the emission spectrum of such a device in a controlled manner. The occurrence of sharp features in the Fourier transformed spectrum allowed the identification of the mode spacing corresponding to the full cavity length, as well as to fractions of the full cavity length due to the etched groove. This enables us to identify additional features in the transform spectrum as being due to scattering centers within the waveguide. Identification of the density and strength of such centers is an important capability for the fabrication of blue diode lasers in the gallium–nitride material system.